Retorno presencial na pandemia da covid-19:ações das professoras alfabetizadoras e de políticas públicas - Placeres, Mariane Ferreira (Universidade Federal de São Carlos, 2024)
The novel coronavirus (COVID-19) pandemic has led to changes in the organization of life in society, and the school environment has been no different. Teaching had to adapt to the health limitations and during 2020 and much of 2021 it began to be offered remotely. This research sought to identify and analyze the challenges and actions of teachers and the school network aimed at the literacy of students in the second and third years of elementary school after the return to face-to-face classes in the municipal network of Araraquara, São Paulo, surveying the actions implemented by teachers, schools and the school network. The research uses a qualitative approach as its methodological basis and is divided into three stages, the first of which presents the context of literacy before the start of the pandemic, providing some indicators and analyzing the contents of official documents related to literacy, such as the National Education Plan, the National Common Curriculum Base and the National Literacy Policy; the second, a bibliographic survey to expose the difficulties that have arisen in relation to literacy with the pandemic; and the third, semi-structured interviews with five literacy teachers, presenting the challenges encountered in the return to face-to-face classes and the survey of actions to face the difficulties that have arisen. Through the interviewees' speeches, the following thematic axes could be identified: "previous scenario - accentuation of the precariousness of teaching work and the quality of education during remote teaching", "return to face-to-face classes - absences and the relationship between family and school", "pedagogical and psychological challenges of returning to face-to-face classes", "heterogeneity of classes and tutoring", "reactions to the municipal policies of Educa Mais", "teaching the unlearned - the challenges and actions aimed at students with more difficulty". The aim was to investigate the policy initiatives of the network, the school and especially the teachers, as well as to discuss strategies aimed at literacy.
In-person return during the Covid-19 pandemic: actions of literacy and public policy teachers
Keywords: Alfabetização; Pandemia de COVID-19; Ensino remoto emergencial; Políticas públicas; Ações docentes; Literacy; COVID-19 pandemic; Emergency remote teaching; Public police; Teaching action; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM